2014
DOI: 10.1371/journal.pone.0103424
|View full text |Cite
|
Sign up to set email alerts
|

Electrophysiological Explorations of the Bilingual Advantage: Evidence from a Stroop Task

Abstract: Bilinguals have been shown to exhibit a performance advantage on executive control tasks, outperforming their monolingual counterparts. Although a wealth of research has investigated this ‘bilingual advantage’ behaviourally, electrophysiological correlates are lacking. Using EEG with a Stroop task that manipulated the stimulus onset asynchrony (SOA) of word and colour presentation, the current study addressed two facets of the bilingual advantage. The possibility that bilinguals experience superior conflict pr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

3
67
0

Year Published

2015
2015
2023
2023

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 49 publications
(70 citation statements)
references
References 113 publications
(142 reference statements)
3
67
0
Order By: Relevance
“…In contrast, the Stroop task showed greater P3 amplitudes for monolinguals than bilinguals. Similarly, Coderre et al . reported greater P3 amplitudes for monolinguals than bilinguals during a Stroop task.…”
Section: Earlier and More Automatic Processes In Bilingualsmentioning
confidence: 82%
See 1 more Smart Citation
“…In contrast, the Stroop task showed greater P3 amplitudes for monolinguals than bilinguals. Similarly, Coderre et al . reported greater P3 amplitudes for monolinguals than bilinguals during a Stroop task.…”
Section: Earlier and More Automatic Processes In Bilingualsmentioning
confidence: 82%
“…These ERP effects suggest that monolinguals might be devoting more resources at late stages of processing (interference control and response selection) than bilinguals to deal with conflict. In another study, Coderre et al . examined the N450 and found that bilinguals had smaller ERP Stroop effects than monolinguals with equal behavioral performance, again demonstrating that monolinguals are devoting more resources at late stages of processing compared with bilinguals.…”
Section: Earlier and More Automatic Processes In Bilingualsmentioning
confidence: 99%
“…For example, group differences in eye-movement patterns (even in the absence of behavioral reaction time differences) may suggest that bilinguals and monolinguals employ distinct search strategies. Because bilinguals excel at focusing on task-relevant information (e.g., Coderre & Van Heuven, 2014), we expected eye-movements to reflect bilinguals’ ability to ignore non-target objects.…”
mentioning
confidence: 99%
“…This provides limited evidence for the presence of a confl ict-specifi c bilingual advantage. However, Coderre & van Heuven ( 2014a ) also observed group differences between bilinguals (in both languages) and monolinguals when comparing control trials, which contained no confl icting or facilitating information. Furthermore, these group differences observed in the negative SOA before the color had been presented, i.e.…”
Section: Neuroimaging Evidence For the Bilingual Advantagementioning
confidence: 86%
“…The irrelevant distractor word could either appear just before the target color (a 'negative SOA'); just after (a 'positive SOA'; or at the same time (a '0 ms SOA'). Coderre & van Heuven ( 2014a ) found some signifi cant, but inconsistent, differences between monolinguals and bilinguals in a confl ict-related ERP component (the Ninc): bilinguals showed differences compared to monolinguals when performing this Stroop task in their L1 but not their L2. This provides limited evidence for the presence of a confl ict-specifi c bilingual advantage.…”
Section: Neuroimaging Evidence For the Bilingual Advantagementioning
confidence: 96%